Plasma Cell‐Free DNA Genotyping: From an Emerging Concept to a Standard‐of‐Care Tool in Metastatic Non‐Small Cell Lung Cancer. (26th July 2021) - Gray, Jhanelle; Thompson, Jeffrey C.; Carpenter, Erica L.; Elkhouly, Ehab; Aggarwal, Charu
Abstract: Plasma cell‐free DNA (cfDNA) genotyping is an alternative to tissue genotyping, particularly when tissue specimens are insufficient or unavailable, and provides critical information that can be used to guide treatment decisions in managing patients with non‐small cell lung cancer (NSCLC). In this article, we review the evolution of plasma cfDNA genotyping from an emerging concept, through development of analytical methods, to its clinical applications as a standard‐of‐care tool in NSCLC. The number of driver or resistance mutations recommended for testing in NSCLC continues to increase. Because of the expanding list of therapeutically relevant variants, comprehensive testing to investigate larger regions of multiple genes in a single run is often preferable and saves on time and cost, compared with performing serial single‐gene assays. Recent advances in nucleic acid next‐generation sequencing have led to a rapid expansion in cfDNA genotyping technologies. Analytic assays that have received regulatory approval are now routinely used as diagnostic companions in the setting of metastatic NSCLC. As the demand for plasma‐based technologies increases, more regulatory approvals of cfDNA genotyping assays are expected in the future. Plasma cfDNA genotyping is currently aiding oncologists in the delivery of personalized care by facilitating matching of patients with targeted therapy and monitoring emergence of resistance to therapy in NSCLC. Further advances currently underway to increase assay sensitivity and specificity will potentially expand the use of plasma cfDNA genotyping in early cancer detection, monitoring response to therapy, detection of minimal residual disease, and measurement of tumor mutational burden in NSCLC. Implications for Practice: Plasma cell‐free DNA (cfDNA) genotyping offers an alternative to tissue genotyping, particularly when tissue specimens are insufficient or unavailable. Advances in cfDNA genotyping technologies have led to analytic assays that are now routinely used to aid oncologists in the delivery of personalized care by facilitating matching of patients with targeted therapy and monitoring emergence of resistance to therapy. Further advances underway to increase assay sensitivity and specificity will potentially expand the use of plasma cfDNA genotyping in early cancer detection, monitoring response to therapy, detection of minimal residual disease, and evaluation of tumor mutational burden in non‐small cell lung cancer. Abstract : This article reviews the evolution of plasma cell‐free DNA genotyping from an emerging concept, through development of analytical methods, to its clinical applications as a standard‐of‐care tool in non‐small cell lung cancer.